(untitled) (Applied Biological Research, 2022)
The present study was aimed to assess the prevalence of phenylthiol carbamide (PTC) taste sensitivity, and its relation with obesity among the male and female population of Udaipur, Rajasthan (India). The study was carried out on 235 individuals (94 males and 141 females) aged ≥ 40 years. The food preferences were recorded through personal interview method, and standard anthropometric procedures were followed to measure anthro pometric variables. Body mass index (BMI) and waist to hip ratio (WHR) were also calculated. The subjects were asked to taste PTC solution and classified as tasters and non-tasters. The overall tasters among the studied population were 169 (71.9%). Distribution of PTC taste sensitivity were more frequent among female (taster = 60.35%, non-taster = 59.09%) than male (taster = 39.6%, non-taster = 40.9%). The PTC taster’s both male and female, showed higher BMI as compared to the non-taster individuals. Considering the life style variables, the smoking status showed a significant difference between tasters and non-tasters (χ2 = 3.97; p = 0.047), but no difference was observed for alcohol consumption (χ2 = 0.77; p = 0.381). The present study provides background information about PTC taste sensitivity’s phenotypic frequency distribution which may serve as useful interactions of taste sensitivity with other associated lifestyle variables.